Guard-Cell Hexokinase Increases Water-Use Efficiency Under Normal and Drought Conditions - Kelly, Gilor; Egbaria, Aiman; Khamaisi, Belal; Lugassi, Nitsan; Attia, Ziv; Moshelion, Menachem; Granot, David (Frontiers in Plant Science, 2019)
Water is a limiting resource for many land plants. Most of the water taken up by plants is lost to the atmosphere through the stomata, which are adjustable pores on the leaf surface that allow for gas exchange between the plant and the atmosphere. Modulating stomatal activity might be an effective way to reduce plants’ water consumption and enhance their productivity under normal, as well as water-limiting conditions. Our recent discovery of stomatal regulation by sugars that is mediated by guard-cell hexokinase (HXK), a sugar-sensing enzyme, has raised the possibility that HXK might be used to increase plant water-use efficiency (WUE; i.e., carbon gain per unit of water). We show here that transgenic tomato and Arabidopsis plants with increased expression of HXK in their guard cells (GCHXK plants) exhibit reduced transpiration and improved WUE without any negative effects on growth under normal conditions, as well as improved performance under limited-water conditions. Our results demonstrate that exclusive expression of HXK in guard cells is an effective tool for improving WUE, and plant performance under drought.